Identification and Evaluation of Options for Specialist Disability Housing for Clients with a Range of Needs and Disabilities - Ong, R; Haslam McKenie, F; Greive, S (My University, 2010)
The objective of this research is to identify the likely demand for housing for people with disabilities and to evaluate potential structural arrangements between the specialist disability services sector and the Department of Housing so as to maximise the availability of appropriate housing stock for people with disabilities. This report focuses on a distinct group of people within the disability sector, those who make up the core demand for housing based support. The report considers several key research questions which can be broadly classified under three inter-linked overarching objectives.
Keywords: Health -- Disability; Health; Housing; Health and wellbeing; Housing; Health; Disability; Health and wellbeing